2003
DOI: 10.1128/mcb.23.13.4663-4672.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Bcr Kinase Downregulates Ras Signaling by Phosphorylating AF-6 and Binding to Its PDZ Domain

Abstract: The protein kinase Bcr is a negative regulator of cell proliferation and oncogenic transformation. We identified Bcr as a ligand for the PDZ domain of the cell junction and Ras-interacting protein AF-6. The Bcr kinase phosphorylates AF-6, which subsequently allows efficient binding of Bcr to AF-6, showing that the Bcr kinase is a regulator of the PDZ domain-ligand interaction. Bcr and AF-6 colocalize in epithelial cells at the plasma membrane. In addition, Bcr, AF-6, and Ras form a trimeric complex. Bcr increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 50 publications
6
113
0
Order By: Relevance
“…Recent studies have suggested that Bcr localizes to the plasma membrane at the cellular junctions of epithelial cells (34,42). Therefore, possible transient changes in Bcr and Abr localization could occur depending on the cell type and stimulus.…”
Section: Combined Loss Of Abr and Bcr Results In A Synergistic Increamentioning
confidence: 99%
“…Recent studies have suggested that Bcr localizes to the plasma membrane at the cellular junctions of epithelial cells (34,42). Therefore, possible transient changes in Bcr and Abr localization could occur depending on the cell type and stimulus.…”
Section: Combined Loss Of Abr and Bcr Results In A Synergistic Increamentioning
confidence: 99%
“…This motif has been shown to be important for its subcellular localizations and/or its interactions with other PDZ domain-containing proteins to maintain certain structures of cytoskeleton, a process that is important for Ras transformation (51,52). Moreover, these interactions are also regulated by protein phosphorylations and dephosphorylations (51,53).…”
Section: Discussionmentioning
confidence: 99%
“…3), and was originally identified as a fusion partner of the ALL-1 gene involved in acute lymphoblastic leukaemia 4 . AF6 is a multi-domain protein, consisting (from the N to C terminus) of two Ras-associating domains, a forkhead-associated domain, a dilute domain, a PDZ (PSD95/Dlg1/ZO-1) domain and three proline-rich regions (Pro) [5][6][7] . In rodents and humans, AF6 is expressed in almost all epithelial tissues 8 mainly with two isoforms: a long isoform containing the F-actin-binding domain (FA) and a short isoform lacking the FA domain; these versions are referred to as l-and s-afadin, respectively.…”
mentioning
confidence: 99%